PENGARUH PENERAPAN DEEP LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS MATERI KEARIFAN LOKAL MADURA DI SDN PATEREMAN 1 - Dwi safitri; Priyono Tri Febrianto; Firdausi Nurharini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students’ critical thinking skills in IPAS learning are still relatively low, especially in topics related to local wisdom. This study aims to determine the effect of applying the Deep Learning approach on students’ critical thinking skills in IPAS learning with the topic of Madurese Local Wisdom at SDN Patereman 1. This research employed an experimental method with a pre-experimental One Group Pretest-Posttest design. The study was conducted in grade IV with a total sample of 29 students using a saturated sampling technique. The instruments used were pretest and posttest in the form of multiple-choice questions. Data were collected through observation, tests, and documentation. The data analysis techniques used were normality test and paired sample t-test. Based on the analysis using SPSS 27 for Windows, the average pretest score was 62.41 and the average posttest score was 76.90, showing an improvement of 14.49 points after the implementation of Deep Learning through the Problem Based Learning model. The results of the paired sample t-test showed a significance value (Sig. 2-tailed) of <0.001 <0.05 and a t-value of -6.471, indicating that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the application of the Deep Learning approach has a significant effect on improving students’ critical thinking skills in IPAS learning on the topic of Madurese Local Wisdom at SDN Patereman 1.